Trends in undiagnosed HIV-1 infection among attenders at genitourinary medicine clinics, England, Wales, and Northern Ireland: 1990-6. Issue 5 (1st October 1999) - Simms, I; Rogers, P; Catchpole, M; McGarrigle, C A; Nicoll, A
Abstract : OBJECTIVE: To describe trends in seroprevalence of undiagnosed HIV-1 infection among attenders at 15 genitourinary medicine clinics in England, Wales, and Northern Ireland between 1990 and 1996. METHOD: Prospective, cross sectional sentinel serosurvey. Unlinked anonymous testing of remnant serum drawn for routine syphilis screening. RESULTS: In 1996, the seroprevalence of undiagnosed HIV-1 infection was 5% in homosexual men, 0.48% in heterosexual men, and 0.33% in heterosexual women. Between 1990 and 1996, there was a significant linear decrease in the seroprevalence of undiagnosed HIV-1 infection among homosexual and bisexual men within and outside London (p < 0.0001; p = 0.0141), equivalent to yearly decreases of 7.65% and 10.73% respectively. However, seroprevalence among homosexual and bisexual men under 25 years of age did not decline either inside or outside London. Seroprevalence among heterosexual men declined outside London (p < 0.005), equivalent to an average annual decrease of 14.54%. There was a significant increase among male heterosexuals inside London (p < 0.05) equivalent to a 8.09% increase per annum. Seroprevalence over time was unchanging among female heterosexuals both inside and outside London. Seroprevalence was significantly higher among those who injected drugs than those who did not report injecting in the following groups: homosexual and bisexual males within London (p < 0.005), male heterosexuals both within and outside London (p < 0.05; p < 0.05) and female heterosexuals within London (p < 0.05). CONCLUSIONS: The study highlights a significant burden of undiagnosed HIV-1 infection more than 15 years since the HIV epidemic began. Methods of offering HIV testing need to be reassessed to extend the practice of routinely testing for HIV in GUM clinics. HIV transmission among young homosexual and bisexual men continues. The contrasting trends between homosexual and bisexual men, injecting drug users, and heterosexuals attending GUM clinics indicate these groups should be considered separately. The substantial HIV seroprevalence in each group indicates that they should be priorities for targeted HIV prevention.